Short-term variation in phytoplankton and zooplankton assemblages across a seaweed- farming coastal gradient in Galesong, Sulawesi, Indonesia - Rahmat Pratama Putra; Nur Halizah Roebetho; Putri Sakinah Resman; Andi Alya Yusriyyah; Amanda Pricella Putri; Asmi Citra Malina; Nita Rukminasari; Irmawati; Jamaluddin Fitrah Alam (BRIN Publishing (Penerbit BRIN), 2026)
Information on short-term variation in phytoplankton and zooplankton assemblages in tropical seaweed farming environments is still limited. This study aimed to characterize the taxonomic composition, abundance, diversity and weekly spatial patterns of phytoplankton and zooplankton along a nearshore-seaweed farm-offshore gradient in Galesong, South Sulawesi, Indonesia. Sampling was carried out once a week for six consecutive weeks at three permanent stations representing nearshore waters, active Kappaphycus alvarezii farm and offshore waters. Samples were analyzed by means of Inverse Distance Weighted (IDW) interpolation to determine the microscopic identification, ecological indices and spatial distribution mapping. The total number of phytoplankton taxa was 10 and the assemblage was dominated by the diatoms Chaetoceros sp. and Leptocylindrus sp. The phytoplankton abundance was always higher than the zooplankton abundance and the Shannon–Wiener diversity ranged from 1.67 to 1.99. Five zooplankton taxa were recorded with unidentified crustaceans, Tintinnopsis sp. and Balanus larvae being numerically dominant. Zooplankton Shannon-Wiener diversity ranged from 1.02 to 1.09. The offshore station had highest total abundance in Weeks 1–3, the nearshore station had highest values in Weeks 4–6, and the seaweed-farm station did not show a consistently unique pattern of abundance or diversity. This pattern suggests that environmental variability may cause redistribution of plankton assemblages, although the mechanisms were not directly tested in this study. These results offer a preliminary baseline of phytoplankton and zooplankton assemblages in the region of study. Future studies should incorporate greater spatial and seasonal sampling and environmental measurements to better understand factors influencing plankton variability.